Improving Maternal Health through Nutrition Education and Home-Based Prenatal Mobilization Program - Astri - Anita; Dwi Hardiyanti (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
ABSTRACTPregnant women are vulnerable to health risks such as anemia, nutrient deficiencies, and musculoskeletal complaints. This community service aimed to improve maternal knowledge and healthy behaviors through nutrition education and home-based prenatal mobilization using the In-House Training (IHT) method. The program involved all pregnant women registered at Puskesmas Bungoro, with interventions including education on iron tablet consumption, foods rich in iron and vitamin C, pelvic and postural exercises, breathing techniques, and stress and rest management. Evaluation was conducted descriptively through direct observation and interviews. Results showed significant improvements in maternal knowledge and behaviors, including adherence to iron tablet consumption increasing from 40% to 82% and practice of prenatal mobilization exercises from 35% to 78%. These findings indicate that home-based, personally guided education with direct demonstration and interactive guidance effectively enhances maternal health awareness and promotes positive behavioral change. The program is recommended as a practical model for promotive and preventive maternal health interventions at primary health care facilities.Ibu hamil rentan terhadap risiko kesehatan seperti anemia, kekurangan nutrisi, dan keluhan muskuloskeletal. Pengabdian masyarakat ini bertujuan meningkatkan pengetahuan dan perilaku sehat ibu hamil melalui edukasi nutrisi dan mobilisasi prenatal di rumah dengan metode In-House Training (IHT). Program mencakup edukasi konsumsi tablet tambah darah, makanan tinggi zat besi dan vitamin C, latihan panggul dan postur, teknik pernapasan, serta manajemen stres dan istirahat. Evaluasi dilakukan secara deskriptif melalui observasi langsung dan wawancara singkat. Hasil menunjukkan peningkatan signifikan pada pengetahuan dan perilaku ibu hamil, termasuk kepatuhan konsumsi tablet tambah darah dari 40% menjadi 82% dan praktik latihan mobilisasi prenatal dari 35% menjadi 78%. Temuan ini menunjukkan bahwa edukasi di rumah dengan pendampingan personal, demonstrasi langsung, dan interaksi dua arah efektif meningkatkan kesadaran kesehatan ibu serta mendorong perubahan perilaku positif. Program ini dapat dijadikan model praktis untuk intervensi promotif dan preventif kesehatan ibu hamil di fasilitas pelayanan kesehatan primer.